MEDIATIC AESTHETIC VERSUS PROFESSIONAL FORMATION IN PHYSICAL EDUCATION: A COMPARATIVE STUDY BETWEEN BRAZIL AND CHINA (Fiep Bulletin - online, 2014)
This paper had as an aim to analyze Physical Education professionals' perception of media discourse regarding physical exercise. The Qualitative Interpretative approach was used, in which two collaborators participated of the research, one Brazilian and the other Chinese. From the interviews three categories were defined: body and media, professional intervention, knowledge construction. The conclusions were: a) there is professional conscience both in Brazil and China; b) there is professional intervention as for students' doubts in both countries; c) Media dictates the quest for slimness; d) the Physical Education teacher is more valorized in China than in Brazil.
Keywords: professional intervention; media; aesthetic